2022
DOI: 10.1186/s12014-022-09348-y
|View full text |Cite|
|
Sign up to set email alerts
|

A novel non-invasive method allowing for discovery of pathologically relevant proteins from small airways

Abstract: Background There is a lack of early and precise biomarkers for personalized respiratory medicine. Breath contains an aerosol of droplet particles, which are formed from the epithelial lining fluid when the small airways close and re-open during inhalation succeeding a full expiration. These particles can be collected by impaction using the PExA® method (Particles in Exhaled Air), and are derived from an area of high clinical interest previously difficult to access, making them a potential sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Results from the present study focussing on differences between subjects with asthma with and without small airway dysfunction and healthy controls (HC), respectively, have been presented earlier [20]. During the analyses of protein profiles in exhaled particles, it has been evident that proteins belonging to the complement and coagulation systems are overrepresented and seem of particular interest, both in the present study and also in another study population including smokers [21].…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Results from the present study focussing on differences between subjects with asthma with and without small airway dysfunction and healthy controls (HC), respectively, have been presented earlier [20]. During the analyses of protein profiles in exhaled particles, it has been evident that proteins belonging to the complement and coagulation systems are overrepresented and seem of particular interest, both in the present study and also in another study population including smokers [21].…”
Section: Introductionsupporting
confidence: 53%
“…SOMAscan (SomaLogic Inc, Boulder, USA) is an aptamer-based proteomics platform that uses slow off-rate-modified DNA aptamers (SOMAmers) as high-affinity protein capture reagents to quantify proteins. PEx sample preparation and SOMAscan analysis has been previously described in detail [20, 21]. Prior to SOMAscan analysis, the volume of sample buffer was adjusted to reach the same concentration of PEx in all samples in order to normalize the samples for the differences in the collected amount of PEx.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to particle flow rate, samples can be analysed through mass spectrometry for lipidomics or enzyme-linked immunosorbent assay (ELISA) for proteomics to establish the chemical composition of the small airways, allowing differences to be established between physiology and pathology [19]. Particles sampled and assessed through PExA have considerable potential; Bredberg et al (2012) identified 120 different proteins that can be detected, with up to 80% being concurrently detected via invasive bronchoscopy, and Östling et al identified 207 proteins from PExA samples, with phenotypic distributions depending on the smoking status [37]. An additional advantage of using PExA (in comparison to both BAL and tracheal aspirate) is that it does not involve administering foreign substances into the respiratory system that can alter or dilute the respiratory fluid composition [13].…”
Section: Pexa Basicsmentioning
confidence: 99%
“…and Östling et al identified 207 proteins from PExA samples, with phenotypic distributions depending on the smoking status [37]. An additional advantage of using PExA (in comparison to both BAL and tracheal aspirate) is that it does not involve administering foreign substances into the respiratory system that can alter or dilute the respiratory fluid composition [13].…”
Section: Pexa Basicsmentioning
confidence: 99%